RELATIONSHIP BETWEEN SOIL–SOIL-SOLUTION DISTRIBUTION COEFFICIENTS OF 125I AND 127I IN PASTURE SOIL. Issue 3 (26th April 2019) - Unno, Y; Takeda, A; Takaku, Y; Hisamatsu, S
Abstract: We measured the depth profiles of soil–soil-solution distribution coefficients ( K d ) of native 127 I ( 127 I- K d ) and exogenous 125 I – ( 125 I- K d ) in soils from a pasture near the spent nuclear fuel reprocessing plant in Rokkasho, Japan, and investigated their relationships to depth profiles of the concentration in soil of 127 I and organic C and K d of organic C (C- K d ). The depth profiles of 125 I- K d and 127 I- K d were similar. The relatively low 127 I concentrations and low values of both 127 I- K d and 125 I- K d indicate that some of the I deposited on the soil surface have been transported to depths greater than 10 cm. On the other hand, high 127 I- K d / 125 I- K d ratios in the uppermost 10 cm of soil indicate that some of the 127 I bound to that soil could not be exchanged with exogenous 125 I. Although a previous study has shown a power function relationship between 125 I- K d and C- K d, our data show that the relationships of both 125 I- K d and 127 I- K d to C- K d are exponential functions. The reason for these conflicting results is unknown. Nonetheless, our data clearly show K d values for both 125 I – and 127 I to be dependent on C- K d . In addition, the dependence of both 127 I- K d and 125 I- K d on C- K d suggests that organic material in the soil has a role in the transport of I down the soil profile.